Pelatihan Peningkatan Keterampilan Menggunakan Microsoft Acces Bagi Siswa SMK Pangeran Antasari Untuk Pengolahan Data - Silvia Lestari; Dani Manesah; Suryanto Suryanto; Muhsin Lambok Ilvira; Leni Deli; Afandi Maulana; Lutfi Zaidi (Ekspresi : Publikasi Kegiatan Pengabdian Indonesia, 2025)
This training aims to enhance the skills of students at SMK Pangeran Antasari in using Microsoft Access as a tool for data processing. In today's digital era, mastering database software is a crucial competency, especially for vocational school students who are being prepared to enter the workforce. The training methods included lectures, demonstrations, and hands-on practice using a participatory approach. The materials covered an introduction to databases, table creation, relationships between tables, queries, forms, and basic reporting. The results of the training indicated an improvement in students' understanding and ability to process data using Microsoft Access. Through this program, students are expected to gain practical knowledge in managing data systematically and efficiently, as well as applying it in academic tasks and real-world industry settings.